Analisis Produktivitas Tenaga Kerja pada Pekerjaan Plesteran Dinding dengan Metode Work Study - Jaharuddin, Nadia; Masthura, Lely; Firdasari, Firdasari (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
A highly productive workforce is essential for a construction project to be successful because worker productivity has a significant impact on the final outcome, especially in the construction industry. Wall plastering is an example of a profession that requires hard work. The aim of this research is to calculate the productivity coefficient for plastering work and compare it with the 2022 Indonesian National Standard Work Unit Price Analysis (AHSP SNI) in order to measure the efficiency of wall plastering at work sites. This research was carried out by collecting primary data regarding the efficiency of plastering work at the Basic Laboratory Building at Samudra University through field observations and interviews. Productivity factor analysis of wall plastering work shows an average of 47.61 m2 per day for foremen and head craftsmen, 13.88 m2 per day for craftsmen, and 22.72 m2 per day for assistant craftsmen. Apart from that, the foreman and head craftsman produce 66.66 m2 per day, the craftsman produces 6.66 m2 per day, and the assistant craftsman produces 3.33 m2 per day according to SNI AHSP. Thus, the difference in percentages obtained for the foreman and head craftsman respectively is 28.57%, for the craftsman 52.01%, and for the assistant craftsman 85.34%. Key words:Builder Productivity, Wall Plastering, Building Projects.